P058 Online Feedback: Perceptions About Family Planning in Men and Women With IBD in Brazil. (December 2019) - Lima, Fernanda; Machado, Marta
Abstract : BACKGROUND: Inflammatory Bowel Disease (IBD) predominantly affects young and reproductive age patients. Fears that IBD itself and/or its medication may inadvertently affect stroke, pregnancy outcome and lactation safety are a significant concern for IBD patients. Myths and lack of proper education can make patients voluntarily choose not to have children, stop treatment during pregnancy and refuse lactation. The voluntary lack of children and the constitution of smaller families has been observed and reported in IBD. There is a lack of studies on the perceptions of patients in this scenario in Brazil. The objectives were to evaluate what are the perceptions about family planning in men and women with inflammatory bowel disease. METHODS: This prospective study was conducted by a self-completed cross-sectional online questionnaire answered by 951 female and male IBD patients over 18 years of age throughout Brazil in 2019 for 10 weeks. RESULTS: A total of 951 patients answered the questionnaire, 80% (761) of the questionnaires were usable. The respondent population was 76.34% female, of these 76.38% aged between 18 and 38 years, 57.29% were diagnosed with Crohn's disease, 38.54% ulcerative colitis and 4.17% colitis. undetermined. Regarding the male data, a total of 23.66% of the sample, 78.2% were between 18 and 38 years old; 69.67% were diagnosed with Crohn's disease, 27.96% ulcerative colitis and 2.37% indeterminate colitis. In both genders, female and male consecutively, 49.14/42.48% were using contraception, 41.75/50.24% had children, 50.39 / 33.02% did not plan pregnancy, 58, 10/47.57 had only one child, 30.77/28.78%, the disease disrupted family planning, 67.08/70.37% did not consider having more children, 73.22/87.56% reported that their doctors never addressed family planning during treatment and 43.73/13.81% proactively approached the issue with their doctors. CONCLUSION(S): It can be seen from the data presented that the theme of family planning is little explored by both doctors and patients, and that inflammatory bowel disease can influence family planning with regard to not having children or considering having more children.